Long term influence of alternative corn cropping practices and corn-hay rotations on soil health, yields and forage quality - White, Alissa; Darby, Heather; Ruhl, Lindsey; Sands, Bryony (Frontiers in Environmental Science, 2023)
Modifications to continuous corn production systems can reduce environmental impacts and soil degradation, yet the social viability of these modifications is linked to the degree to which they also influence yields and crop quality. In this study, we focus on forage production systems and evaluate how yields, crop quality, soil health indicators, and associated ecosystem services are influenced by corn-hay rotation treatments, cover cropping, and tillage reduction in silage production using a unique 10-year dataset from Borderview Research Farm in Vermont, USA. Physical, chemical, and biological soil health indicators were monitored annually alongside yields and crop quality in a randomized complete block design experiment. We use a mixed model analysis of variance approach to demonstrate significant influences of time and treatments on yields, crop quality and soil health parameters (at p<0.05). The winter rye cover crop treatment had no significant influence in this study. No-till significantly increased aggregate stability and had no significant effect on other metrics. When cover crop and no-till were combined, they significantly increased soil organic matter content, respiration and aggregate stability. The cover crop, no-till, and no-till cover crop combination treatments had no significant effect on yields or forage quality, suggesting these conservation practices can be adopted without sacrificing yields. Our study also found that corn-hay rotations can significantly increase soil organic matter, respiration, aggregate stability, and crude protein content compared to continuous corn, but they can negatively influence active carbon, total dry matter yield and digestibility. The length of rotation influences the degree to which corn-hay rotations maintain or reduce yields when compared to continuous corn. Shorter rotations of perennial forages (4 years of hay, 6 years of corn) can sustain dry matter yields that are not significantly different from continuous corn, but longer perennial forage rotations (8 years of hay, 2 years of corn) will significantly reduce overall dry matter yields. Among the treatments, no-till in combination with cover cropping in corn silage fields, and a rotation of 4 years of hay to 6 years of corn are likely to achieve the greatest overall benefits in forage production systems.